The Influence of the Lineament Geological Features on the Hydrologic Flow Direction of Wadi Al Kuf Catchment Area, Cyrenaica, Northeastern Libya - Ammar, Ammar A (Al-Mukhtar Journal of Sciences, 2019)
Wadi Al Kuf Catchment Area WKCA is one of the largest watershed basins on Al Jabal al Akhdar Cyrenaica anticlinorium, the area is more than 960Km2, and considers as a semi-wet basin. This basin highly affected with lineaments geological features just like morphometric and tectonics types including fissures, fault systems and joints set systems in the highly karst lime stones of Al Jabal al Akhdar group lithological formations. These lineaments phenomena were measured and extracted from the radar images of digital terrain model of 30 meters space grid, and the hyper spectral Landsat 8 of 15 meters pixel resolution, they were processed and interpreted by several geospatial geomatics and geological software. The direction orientation and the rock density of these fissures, fractures, joints set systems, faults and the morphometric dendritic drainage pattern had been measured and illustrated from the rose diagram analysis and the geological map. The mainstream of this catchment area WKCA is the 6th order and mainly parallel to the main trend direction with the first escarpment circular fault at the major orogeny tectonic fault of Al Jabal al Akhdar uplift, and these lineaments features is averaged 58.3o with the azimuth degree along the mainstream. The drainage density, lineaments density analysis and distribution of the WKCA have been classified as low lineaments rock fractures in the eastern boundary of the basin, moderate lineaments rock fissures in the middle of the basin and high density of rock fracture in the western and northern boundary of the basin, these had reflected the deep percolations and infiltrations to the ground water-bearing aquifer in the WKCA through the secondary and the tertiary porosity of the hydrological karst system.